DOES THE RANK-SIZE RULE MATTER IN INDONESIA? DETERMINANTS OF THE SIZE DISTRIBUTION OF CITIES - Firdaus, Muhammad; Fitria, Annisa (Journal of Indonesian Economy and Business, 2010)
In Indonesia the cities have continously grown. However they varied in size. SomeÂ cities have the population above two million citizens, while some have below than fivehundred thousands. Some economic factors are hypothesized to influence suchÂ distribution. This study aims to test the rank-size rule (Zipfâs law) and to find thedeterminants of size distribution of cities. The panel data method is employed to satisfy theÂ objectives of study. All district and provincial level data are used for year 1995, 2000 andÂ 2005. The pareto exponent shows that the rank-size rule does not matter in Indonesia.Level of agglomeration economies, local government expenditure and number ofÂ administrative city increases the concentration of size of cities. The labor forceÂ participation and regionâs openness affects the size of cities to be more equally distributed.Keywords: cities, rank-size rule, Zipfâs law, pareto exponent, panel data